2015
DOI: 10.1002/pds.3746
|View full text |Cite
|
Sign up to set email alerts
|

Use of quinine and mortality‐risk in patients with heart failure—a Danish nationwide observational study

Abstract: Use of quinine was common and associated with increased mortality in heart failure, especially if administered together with β-blockers and shortly after treatment initiation. Mechanisms underlying the findings remain to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The median follow-up period was 22.8 months based on the six studies that reported this information. The median follow-up period was similar in retrospective studies (Dirican et al 2014; Fourrier-Reglat et al 2015; Slavicek et al 2014; Tahover et al 2015) and prospective studies (Kozloff et al 2010, 2011; Parakh et al 2015; Rouyer et al 2016), with 23.2 months and 22.5 months, respectively. In addition to the targeted therapies, which were bevacizumab or cetuximab, chemotherapy regimens included single-agent therapy (IV 5-fluorouracil or oral capecitabine) and/or combination therapy (mainly FOLFOX, FOLFIRI, XELOX, or XELIRI).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The median follow-up period was 22.8 months based on the six studies that reported this information. The median follow-up period was similar in retrospective studies (Dirican et al 2014; Fourrier-Reglat et al 2015; Slavicek et al 2014; Tahover et al 2015) and prospective studies (Kozloff et al 2010, 2011; Parakh et al 2015; Rouyer et al 2016), with 23.2 months and 22.5 months, respectively. In addition to the targeted therapies, which were bevacizumab or cetuximab, chemotherapy regimens included single-agent therapy (IV 5-fluorouracil or oral capecitabine) and/or combination therapy (mainly FOLFOX, FOLFIRI, XELOX, or XELIRI).…”
Section: Resultssupporting
confidence: 57%
“…In addition to the targeted therapies, which were bevacizumab or cetuximab, chemotherapy regimens included single-agent therapy (IV 5-fluorouracil or oral capecitabine) and/or combination therapy (mainly FOLFOX, FOLFIRI, XELOX, or XELIRI). Among the 11 included studies, 5 used age categories other than ≥ 70 years vs. < 70 years or 65–75 years vs. ≥ 75 years (Dirican et al 2014; Fukuchi et al 2013; Fourrier-Reglat et al 2015; Parakh et al 2015; Sahm et al 2016). The median duration of therapy was reported in seven studies and ranged from 7 (Dirican et al 2014; Hofheinz et al 2014) to 9.97 months (Tahover et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also possesses alpha-adrenergic blocking properties that can predispose to hypotension [ 23 ]. In a Danish study of people with heart failure, quinine was associated with an increased risk of death, particularly with concurrent β-blocker therapy [ 24 ]. Side effects of quinine can occur at therapeutic doses and include tinnitus, hearing impairment, headache, nausea, vertigo and visual disturbance [ 8 ].…”
Section: Discussionmentioning
confidence: 99%